Memory and distribution of virus-specific cytotoxic T lymphocytes (CTLs) and CTL precursors after rotavirus infection. - Offit, P A (1991)
The gastrointestinal tract is constantly exposed to a variety of potentially invasive bacteria, viruses, and parasites. The first line of defense against these pathogens is the intestinal mucosal surface, which consists of epithelial cells, intraepithelial lymphocytes (IELs), mucus, and secretory immunoglobulins. In addition, the intestine is a rich source of lymphocytes located within Peyer's patches and the lamina propria. Little is known about the function, memory, trafficking, or origin of intestinal T lymphocytes after intestinal infection. We studied the murine cytotoxic T-lymphocyte (CTL) response to the intestinal pathogen rotavirus (simian strain RRV). Adult mice were inoculated orally or via the hind footpad with RRV; virus-specific cytotoxic activities in intestinal and nonintestinal lymphocyte populations were determined by 51Cr release assays. In addition, virus-specific CTL precursor (CTLp) frequencies were determined by limiting-dilution analysis. IELs containing rotavirus-specific cytotoxic activity were detected after oral but not footpad inoculation and expressed alpha/beta but not gamma/delta cell surface protein; virus-specific CTLs did not appear to arise from CTLp among IELs. In addition, the site at which RRV was presented to the immune system determined the site at which RRV-specific CTLp first appeared. Frequencies of rotavirus-specific CTLp detected in Peyer's patches were 25- to 30-fold greater after oral than after footpad inoculation. However, regardless of the route of inoculation, rotavirus-specific CTLp were distributed throughout the lymphoid system 21 days after infection. Implications of these findings for vaccine design are discussed.